Effects of Soil Properties, Temperature and Disturbance on Diversity and Functional Composition of Plant Communities Along a Steep Elevational Gradient on Tenerife - Ratier Backes, Amanda; Frey, Larissa; Arévalo, José Ramón; Haider, Sylvia (Frontiers in Ecology and Evolution, 2021)
Elevational variation of vegetation has been of interest for centuries, and a prominent example for such pronounced vegetation changes can be found along the steep elevational gradient on Tenerife, Canary Islands, 200 km off the West-African cost. The 3,718-m ascent to the peak of the island volcano, Teide, offers a unique opportunity to investigate associated changes in vegetation. However, elevation is not a directly acting factor, but represents several natural environmental gradients. While the elevational variation of temperature is globally rather uniform and temperature effects on plant communities are well understood, much less is known about the region-specific elevational change of chemical soil properties and their impact on plant communities along elevational gradients. Because human interference takes place even at high-elevation areas, we considered human-induced disturbance as important third factor acting upon plant community assemblages. In our study, we compared the effects of soil properties, temperature and disturbance on species richness, functional identity and functional diversity of plant communities along the elevational gradient on Tenerife. We used pairs of study plots: directly adjacent to a road and in natural vegetation close by. In each plot, we did vegetation relevées, took soil samples, and installed temperature loggers. Additionally, we collected leaf samples to measure leaf functional traits of 80% of the recorded species. With increasing elevation, soil cation concentrations, cation exchange capacity (CEC) and pH decreased significantly, while the soil carbon to phosphorus ratio slightly peaked at mid-elevations. Temperature had the strongest effects, increasing species richness and favoring communities with fast resource acquisition. Species richness was higher at road verges, indicating the positive effect of reduced competition and artificially generated heterogeneity. However, we did not detect road effects on plant functional characteristics. Vice versa, we did not find soil effects on species richness, but increased concentrations of soil cations favored acquisitive communities. Surprisingly, we could not reveal any influence on community functional diversity. The importance of temperature aligns with findings from large-scale biogeographic studies. However, our results also emphasize that it is necessary to consider the effects of local abiotic drivers, like soil properties and disturbance, to understand variation in plant communities.